siRNA-Loaded Hydroxyapatite Nanoparticles for KRAS Gene Silencing in Anti-Pancreatic Cancer Therapy - Dandan Luo; Xiaochun Xu; M. Zubair Iqbal; Qingwei Zhao; Ruibo Zhao; Jabeen Farheen; Quan Zhang; Peiliang Zhang; Xiangdong Kong (MDPI AG, 2021)
Pancreatic carcinoma (PC) is greatly induced by the KRAS gene mutation, but effective targeted delivery for gene therapy has not existed. Small interfering ribonucleic acid (siRNA) serves as an advanced therapeutic modality and holds great promise for cancer treatment. However, the development of a non-toxic and high-efficiency carrier system to accurately deliver siRNA into cells for siRNA-targeted gene silencing is still a prodigious challenge. Herein, polyethylenimine (PEI)-modified hydroxyapatite (HAp) nanoparticles (HAp-PEI) were fabricated. The siRNA of the KRAS gene (siKras) was loaded onto the surface of HAp-PEI via electrostatic interaction between siRNA and PEI to design the functionalized HAp-PEI nanoparticle (HAp-PEI/siKras). The HAp-PEI/siKras was internalized into the human PC cells PANC-1 to achieve the maximum transfection efficiency for active tumor targeting. HAp-PEI/siKras effectively knocked down the expression of the KRAS gene and downregulated the expression of the Kras protein in vitro. Furthermore, the treatment with HAp-PEI/siKras resulted in greater anti-PC cells' (PANC-1, BXPC-3, and CFPAC-1) efficacy in vitro. Additionally, the HAp-PEI exhibited no obvious in vitro cytotoxicity in normal pancreatic HPDE6-C7 cells. These findings provided a promising alternative for the therapeutic route of siRNA-targeted gene engineering for anti-pancreatic cancer therapy.